Implication of Law Number 23 of 2011 On Zakat Institution Governance Based On Sharia Quality Management Principles; A Case Study in Baznas of Jambi Province - Muhammad Zaki; Amiur Nuruddin; Saparuddin Siregar (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractZakat has fully transformed from the realm of charity to the realm of empowerment and development of the people and state. The management of zakat becomes part of the responsibility of the state as a regulator, facilitator, and at the same time, a motivator as evidenced by the birth of Law No. 11/23 concerning Management of Zakat. This study aims to look at the implications of the Zakat Law on the implementation of the principles of sharia quality management in zakat management in Baznas, Jambi Province. This legal study used a normative legal approach and quality management that aims to find out the principles of quality management contained in the zakat management law and its implementation in Baznas, Jambi Province. The data used in this study are primary and secondary data analyzed using descriptive methods. The results of this study indicate that the Zakat Law has not explicitly explained the management of zakat institutions. Baznas Jambi Province has prepared a quality policy for the management of zakat although it has not yet met the principles of quality management as a whole. The implementation of sharia quality management in Baznas will have implications for the realization of good institutional management so that it will realize the mustahik (zakat deserver) welfare and social welfare of the community and will encourage the achievement of zakat management objectives by law or sharia.Keywords: Zakat, Sharia Quality Management, Zakat Law. AbstrakZakat telah sepenuhnya berubah dari ranah amal ke ranah pemberdayaan dan pengembangan rakyat dan negara. Pengelolaan zakat menjadi bagian dari tanggung jawab negara sebagai regulator, fasilitator dan sekaligus motivator yang dibuktikan dengan lahirnya UU No. 11/23 tentang Pengelolaan Zakat. Penelitian ini bertujuan untuk melihat implikasi dari UU Zakat pada implementasi prinsip-prinsip manajemen kualitas syariah dalam manajemen zakat di Baznas, Provinsi Jambi. Studi hukum ini menggunakan pendekatan hukum normatif dan manajemen mutu yang bertujuan untuk mengetahui prinsip-prinsip manajemen kualitas yang terkandung dalam hukum manajemen zakat dan implementasinya di Baznas, Provinsi Jambi. Data yang digunakan dalam penelitian ini adalah data primer dan sekunder yang dianalisis menggunakan metode deskriptif. Hasil penelitian ini menunjukkan bahwa UU Zakat belum secara eksplisit menjelaskan pengelolaan lembaga zakat. Baznas Provinsi Jambi telah menyiapkan kebijakan mutu untuk pengelolaan zakat walaupun belum memenuhi prinsip-prinsip manajemen mutu secara keseluruhan. Penerapan manajemen kualitas syariah di Baznas akan berimplikasi pada terwujudnya manajemen kelembagaan yang baik sehingga akan mewujudkan kesejahteraan mustahik (zakat deserver) dan kesejahteraan sosial masyarakat dan akan mendorong tercapainya tujuan pengelolaan zakat oleh hukum atau syariah.Kata kunci: Zakat, Manajemen Kualitas Syariah, Hukum Zakat АннотацияЗакят полностью перешёл из сферы благотворительности в область расширения возможностей и развития людей и государства. Управление закятом становится частью ответственности государства как регулятора, посредника и, в то же время, мотиватора, что подтверждается принятием Закона № 11/23 об управлении закятом. Это исследование направлено на изучение последствия принятия Закона Закята на внедрение принципов управления качеством шариата в управлении Закятом в Базнасе в провинции Джамби. В этом правовом исследовании использовался нормативно-правовой подход и управление качеством, целью которого является выяснение принципов управления качеством, содержащихся в законе об управлении закятом и его применении в Базнасе в провинции Джамби. Данные, использованные в этом исследовании, являются первичными и вторичными данными, проанализированными с использованием описательных методов. Результаты этого исследования указывают на то, что Закон Закята не объясняет явно управление учреждениями Закята. В провинции Джамби Базнас подготовил политику качества для управления закятами, хотя она еще не соответствует принципам управления качеством в целом. Внедрение управления качеством шариата в Базнасе будет иметь значение для реализации хорошего институционального управления, чтобы оно обеспечило благосостояние mustahik (имеющих право на закят) и социальное благосостояние общины, и способствовало бы достижению целей управления закятами в соответствии с законом или шариатом.Ключевые слова: Закят, Шариатское управление качеством, Закятский закон.